El maltrato infantil y su incidencia en el desarrollo socio-afectivo de las niñas y niños del primer grado de educación general básica del centro educativo Emilio Abad de la ciudad de Azogues, provincia del Cañar período 2013 – 2014 - Palacios Occhoa, Angélica Maria (2015)
This thesis refers to CHILD ABUSE AND ITS IMPACT ON SOCIO- EMOTIONAL DEVELOPMENT OF CHILDREN FIRST GRADE OF BASIC EDUCATION GENERAL EDUCATION CENTER "EMILIO ABAD" AZOGUES CITY, PROVINCE OF CAÑAR PERIOD 2013 - 2014. The general objective was: To determine the incidence of child maltreatment in the Socio-Affective Development of Children First Degree General Education Basic Education Center "Emilio Abad" Azogues city. The methods used for the preparation of this research work were: Scientific, Inductive, Inductive-Deductive, Descriptive, Analytical, Synthetic, and Statistical model, the techniques used were: a survey of parents, child abuse test applied to teachers to establish Child Abuse and Ebbe Test León Gross applied to parents to determine the Socio-Affective Development. From the results obtained from the survey of parents concludes that: 69% does not prove child abuse, and 31% yes have child abuse. In addition to the test applied to teachers it was found that 36% showed a slight abuse, 31% receive no characteristics of abuse, 24% exhibited a moderate abuse and 9% show have a serious abuse. Child Abuse by parents is defined as the abuse and neglect that are subject infants. With the application of the test to Ebee León Gross Parents of children from School "Emilio Abad" it resulted that: 53% have a Socio-Affective Development of Highly Satisfactory, Satisfactory 33% and 14% Unsatisfactory. The Socio-Affective Development of children in early childhood affects their future personality.